Knowledge integration in Philippine policies for disaster and climate change management a critical policy analysis - De Rivera, Liberty Pascua (2024)
This article interrogates knowledges inclusion and integration in the Philippines' policies for disaster and climate management. Through the lens of cognitive justice, the research refracts the critical facilities of disaster justice to locate processes that marginalize knowledges in policy texts. It illustrates that place-based knowledges are silenced and rendered inferior to "science" in the grammar of policies, thereby delimiting the degree of engagement of alternative perspectives to governance. The article concludes that disaster justice remains elusive given the enduring underrepresentation of place-based knowledges, voices, and agencies for disaster management in official policy discourses.
Keywords: Emergency management; Policy analysis; Social justice; Social marginality